Ferroptosis and Tumor Drug Resistance: Current Status and Major Challenges - Nie, Zhenyu; Chen, Mei; Gao, Yuanhui; Huang, Denggao; Cao, Hui; Peng, Yanling; Guo, Na; Wang, Fei; Zhang, Shufang (Frontiers in Pharmacology, 2022)
Ferroptosis is a novel type of regulated cell death, whose unique metabolic characteristics are commonly used to evaluate the conditions of various diseases especially in tumors. Accumulating evidence supports that ferroptosis can regulate tumor development, metastasis, and therapeutic responses. Considering to the important role of chemotherapy in tumor treatment, drug resistance has become the most serious challenge. Revealing the molecular mechanism of ferroptosis is expected to solve tumor drug resistance and find new therapies to treat cancers. In this review, we discuss the relationship between ferroptosis and tumor drug resistance, summarize the abnormal ferroptosis in tissues of different cancer types and current research progress and challenges in overcoming treatment resistance, and explore the concept of targeting ferroptosis to improve tumor treatment outcomes.